PENINGKATAN KEMAMPUAN MENULIS MELALUI METODE QUANTUM LEARNING DI SEKOLAH DASAR - Fahrurrozi Fahrurrozi (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
The purpose of this research is to gain the empirical data about learning of writing skill at third class elementary school (SDN Bedahan 01 Sawangan Depok) through quantum learning method, This class action research is hold by using cycle model from Stephen Kemmis and Mc Taggart. This research is done through the following phases: planning, acting, observation, reflecting, and evaluating as the basic of re-planning for the next cycles. The result for every cycle is as follows: the first cycle average of writing composition skills equals to 58.54%, whereas the second cycle raising to 69.37%, and at the third cycle increasing more and more with the average score 76.77%. The implication result of this research shows that quantum learning method motivates the student of the third class of elementary school to learn composition. This method can make the student become self-confidence and proactive in building their imagination and creativity to write in a joyful situation.